SDM Unggul Di Tengah Pandemi COVID-19 Perspektif Tenaga Kerja - Mutmainah Mutmainah; Hartirini Warnaningtyas; Choirum Rindah istiqaroh (JAMER : Jurnal Akuntansi Merdeka, 2021)
The purpose this research are how concept of superior human resource? What strategies can be taken? And why should workforce be superior human resources? Thi research is qualitative wih phenomenological approach. Subject in this research are workforce in industry area at Mojokerto district. For get result of research good quality, this research was carried out for one year. The result of research show that concept of superior human resource are human with eight attitude and behavioral of superior human resources. They are 1) breaking the rule, 2) get started and make a change, 3) create creativity, 4) become a reliable source of information within the unit or company, 5) create innovation, 6) direct others, 7) give inspiration, 8) motivate other work force. Workforce can do some strategies to be superior human resource. They are 1) maintain health, 2) work with health protocol, 3) do company rules, 4) achieve productivity according to company standards, 5) training or education, 6) always want to learn, 7) can find side job. In order to workforce can survive and maintained by company in pandemic and digital era  like this, workforce need to become superior human resource. Superior human resource can value added themselves and they have high competitive power